Corrective Feedback, Self-Esteem and Mathematics Learning Outcomes - R, Zubaidah; Fitriawan, Dona; Yusmin, Edy; Nursangaji, Asep; Mirza, Ade (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
One of the strategies to respond the formative assessment results is corrective feedback. Through corrective feedback, it can be verified and elaborated the part of each items where an error occurs which must be reviewed and corrected by students based on the signs given. The purpose of this research is to review the effect of corrective feedback on formative evaluation and mathematics self-esteem on student’s mathematics learning outcome on junior high school by controlling the prior mathematics knowledge of students. The samples were 120 seventh grade students in junior high school on first semester chosen by using random sampling. The method in this research is quasi experiment by using the design of treatment by level 2 × 2. Data were analyzed by using analysis of covariance (ANCOVA). After controlling the prior mathematics knowledge of students, in general, direct corrective feedback was more suited to increase mathematics learning outcomes on junior high school student than indirect corrective feedback. There was an interaction effect on providing corrective feedback and self-esteem on the mathematics learning outcomes. For the student who have high self-esteem, indirect corrective feedback is more suitable to increase mathematics learning outcomes while for the students who have low self-esteem, direct corrective feedback is more suitable to increase mathematics learning outcomes. It is recommended to the mathematics teachers to provide corrective feedback after provision of formative assessment in their class.